Molecular Characterization of Antibiotic Resistance Determinants in Klebsiella pneumoniae Isolates Recovered from Hospital Effluents in the Eastern Cape Province, South Africa - Joan U. Okafor; Uchechukwu U. Nwodo (Antibiotics, 2023)
Klebsiella pneumoniae (K. pneumoniae) is an opportunistic bacteria responsible for many nosocomial and community-acquired infections. The emergence and spread of antibiotic resistances have resulted in widespread epidemics and endemic dissemination of multidrug-resistant pathogens. A total of 145 K. pneumoniae isolates were recovered from hospital wastewater effluents and subjected to antibiogram profiling. Furthermore, the antibiotic resistance determinants were assessed among phenotypic resistant isolates using polymerase chain reaction (PCR). The isolates showed a wide range of antibiotic resistance against 21 selected antibiotics under 11 classes, with the most susceptible shown against imipenem (94.5%) and the most resistant shown against ampicillin (86.2%). The isolates also showed susceptibility to piperacillin/tazobactam (89.0%), ertapenem (87.6%), norfloxacin (86.2%), cefoxitin (86.2%), meropenem (76.6%), doripenem (76.6%), gentamicin (76.6%), chloramphenicol (73.1%), nitrofurantoin (71.7%), ciprofloxacin (79.3%), amikacin (60.7%), and amoxicillin/clavulanic acid (70.4%). Conversely, resistance was also recorded against tetracycline (69%), doxycycline (56.6%), cefuroxime (46.2%), cefotaxime (48.3%), ceftazidime (41.4%). Out of the 32 resistance genes tested, 28 were confirmed, with [tetA (58.8%), tetD (47.89%), tetM (25.2%), tetB (5.9%)], [sul1 (68.4%), sul1I (66.6%)], and [aadA (62.3%), strA (26%), aac(3)-IIa(aacC2)a (14.4%)] genes having the highest occurrence. Strong significant associations exist among the resistance determinants screened. About 82.7% of the K. pneumoniae isolates were multidrug-resistant (MDR) with a multiple antibiotics resistance index (MARI) range of 0.24 to 1.0. A dual presence of the resistant genes among K. pneumoniae was also observed to occur more frequently than multiple presences. This study reveals a worrisome presence of multidrug-resistant K. pneumoniae isolates and resistance genes in hospital waste effluent, resulting in higher public health risks using untreated surface water for human consumption. As a result, adequate water treatment and monitoring initiatives designed to monitor antimicrobial resistance patterns in the aquatic ecosystem are required.